Predictors of positive response to beta-blockers for treatment of premature ventricular complexes - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2022)
Background: The aim of the present study is to investigate the possible factors that might be predictive of effective antiarrhythmic effect of beta-blockers on premature ventricular complexes (PVC). Methods: Data of 190 eligible consecutive patients to whom beta-blocker therapy had been initiated for treatment of PVC's were retrospectively evaluated. The Holter recording acquired before beta-blocker initiation and the first Holter acquired after beta blocker initiation during follow up was comprehensively evaluated for each patient. Parameters obtained from pre- and post-beta-blocker 24 h Holter recordings were compared with each other and possible predictors were evaluated for positive response to beta-blocker therapy. Results: Sixty-one patients (32.1%) were observed to respond beta-blocker therapy with at least 50% reduction of daily PVC burden. Patients who responded to beta-blockers had significantly higher ratio of patients who had positive correlation between hourly heart rate and corresponding hourly PVC number (fast HR-PVC status) compared with non-responders (73.8% vs 48.1%, p < 0.001). Binary logistic regression analysis revealed PVC QRS width (Odds ratio: 0.971; p: 0.037) and fast HR-PVC status (Odds ratio: 2.935; p: 0.007) as the independent predictors of positive response to beta-blockers for treatment of PVC. Conclusion: Positive correlation between hourly heart rate and PVC incidence was found to be independent positive predictor and PVC QRS width was found to be independent negative predictor of beta-blocker success in our study. This observation might have important clinical implications to guide medical treatment of PVCs in clinical practice.
Keywords: Premature ventricular complex; Beta-blocker; Holter recording; Diurnal variability of premature ventricular; complexes; COUPLING INTERVAL VARIABILITY; HEART-RATE; CONTRACTIONS; SUPPRESSION; SLEEP